H.761 Support of an SVG Media Type - Guedes, Alan L. V.; Colcher, Sergio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
The H.761 standard defines that the NCL media object that is required in a Ginga-NCL implementation is the hypertext markup language (HTML)-based media object. Such HTML media object considerable use of memory and data transmission. Therefore, it is useful for devices with considerable memory and with a broadband connection. However, it is not recommended for scenarios with low bitrate and contrast memory, such as the digital radio device. In such cases, the NCL application used data should be minimum. For such scenarios, the use of graphic media, such as png and jpg, can consume considerable data. We propose that an SVG engine should also be required to support such cases.